PERAN KADER POSYANDU DALAM MENGEMBANGKAN RESILIENSI ORANGTUA YANG MENYANDANG ANAK STUNTING - Atiah, Atiah; Mutaqin, Moh. Fikri Tanzil; Risna, Inten (LPPM Universitas Bina Bangsa, 2024)
Stunting is still a serious public health challenge in Indonesia, with a prevalence reaching 30.8% in children under five according to Riskesdas 2018. In Baros District, the prevalence of stunting will reach 28.5% in 2023. This research aims to examine the role of Posyandu cadres in developing people's resilience parents who have stunted children in Baros District, considering their role is not yet optimal in the psychosocial aspects of parents. Using a qualitative descriptive approach with data collection techniques through interviews, observation and documentation, this research analyzes data through the stages of collection, reduction, presentation and drawing conclusions. The research results show that Posyandu cadres play an important role in developing parental resilience through strengthening belief systems, supporting organizational patterns, and facilitating communication processes. A holistic approach that integrates physical and psychosocial aspects has proven effective in treating stunting. In conclusion, the role of Posyandu cadres is very important in supporting families with stunted children, and ongoing efforts are needed to strengthen their capacity and integrate a holistic approach in stunting management programs. This research contributes to the development of effective intervention strategies to improve the quality of life of families with stunted children and supports efforts to reduce the prevalence of stunting